2014
DOI: 10.1111/1471-0528.12568
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐rectified signal averaging for intrapartum electronic fetal heart rate monitoring is related to acidaemia at birth

Abstract: Objective Recent studies suggest that phase-rectified signal averaging (PRSA), measured in antepartum fetal heart rate (FHR) traces, may sensitively indicate fetal status; however, its value has not been assessed during labour. We determined whether PRSA relates to acidaemia in labour, and compare its performance to short-term variation (STV), a related computerised FHR feature. Design Historical cohort.Setting Large UK teaching hospital.Population All 7568 Oxford deliveries that met the study criteria from Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 16 publications
(43 reference statements)
4
77
1
Order By: Relevance
“…Some studies found that new computerized measures like phase-rectified signal averaging could also predict acidemia at birth with slightly higher predictive ability and better predictive performance than STV [20]. The combination of STV and other computerized features could be a possibility to improve the efficiency of computerized FHR.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that new computerized measures like phase-rectified signal averaging could also predict acidemia at birth with slightly higher predictive ability and better predictive performance than STV [20]. The combination of STV and other computerized features could be a possibility to improve the efficiency of computerized FHR.…”
Section: Discussionmentioning
confidence: 99%
“…From a number of monitoring sessions performed for each patient, we selected only one recording acquired around 1 week before delivery, with a length of at least 30 min (Georgieva et al, 2014). All the recordings are accompanied by information on fetal outcome: gestational age at birth, blood gas parameters pH and BE, percentile of fetal birth weight, Apgar score, information about a possible stay in the NICU.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, various computerised systems for objective FHR analysis have been developed, one of the most validated and used being the Oxford-system 6 , devised by Dawes, Redman and colleagues in 1982 7 . Currently in use today in many antenatal clinics and Day assessment Units, computerised systems eliminate observer variability, improve the reproducibility of EFM, and determine FHR parameters such as short-term variation (STV) that cannot be assessed visually 8 .…”
Section: Introductionmentioning
confidence: 99%